Pan-omics focused to Crick's central dogma - Jaiswal, Arun Kumar; Tiwari, Sandeep; Tavares, Guilherme Campos; Da Silva, Wanderson Marques; Oliveira, Leticia De Castro; Ibraim, Izabela Coimbra; Guimaraes, Luis Carlos; Pinto Gomide, Anne Cybelle; Jamal, Syed Babar; Pantoja, Yan; Tiwary, Basant K.; Burkovski, Andreas; et al. (Pan-genomics: Applications, Challenges, and Future Prospects, 2020)
With the development of next-generation sequencing (NGS) technologies, genome sequencing process has become cheaper and faster, making it possible the use of the technology in daily routine and, as a result, the number of registered genome projects is increasing rapidly. The pan-omics approaches have been applied for comparison of several genomes in a multipronged strategy. The pan-genome is composed of the core genome, shared genome, and singleton subsets, where the core genome is composed of all the commonly shared genes by all strains of the species; shared genome contains genes that are present in two or more, but not all strains from a species; and the singletons are strain-specific genes. The subsets from pan-transcriptomics and pan-proteomics may be classified in the same way. The concept of pan-genomics is so deep that it has been perfectly applied in the studies of several organisms and diseases. It has great potential which may bring a closer understanding and combating with prokaryotic and eukaryotic diseases. In this chapter, we review the concepts of omics, pan-omics, and the areas of applications of these methods.<br
CRIS-Team WoS Importer:2020-09-11
Keywords: Pan-genomics; Pan-transcriptomic; Pan-proteomic; Probiosis; Pan-metagenomics; Pan-cancer